The Influence of Government Policy on the Growth of Technology Startups in Malaysia and Indonesia - Dara Vann; Ravi Dara; Chak Sothy (Yayasan Adra Karima Hubbi, 2024)
The growth of technology startups is crucial to the economic development of emerging economies in Southeast Asia, particularly in Malaysia and Indonesia. Government policies play a significant role in shaping the entrepreneurial landscape by providing the necessary infrastructure, funding opportunities, and regulatory support. Despite the importance of government intervention, there remains a lack of comprehensive studies comparing the impact of government policies on the growth of technology startups in both Malaysia and Indonesia. This study aims to explore the influence of government policies on the development of technology startups in these two countries, examining the differences in approach, implementation, and outcomes. The research utilizes a comparative case study approach, employing both qualitative and quantitative methods. Data were collected through interviews with technology startup founders, government representatives, and industry experts, complemented by a review of secondary data from government reports and startup incubators. The study reveals that government policies in both countries have significantly influenced the growth of technology startups, with Malaysia’s more structured and long-term policy frameworks yielding better results in fostering innovation and scalability. On the other hand, Indonesia’s policies, while supportive, face challenges related to bureaucracy and inconsistent implementation. In conclusion, the research highlights the critical role of government policies in enabling the growth of technology startups. While Malaysia has been more successful in creating a conducive environment for innovation, Indonesia's startup ecosystem requires further policy refinement and consistent enforcement to accelerate growth. These findings offer valuable insights for policymakers and entrepreneurs seeking to enhance the startup ecosystem in Southeast Asia.